Whole Scalp Radiation Therapy for Recurrent Benign Cylindromas - Shivam Kaushik; Danielle Siegel; Kenneth Niermann; Neil Newman (Karger Publishers, 2022)
Cylindromas are a rare benign pathology that can manifest as multiple lesions on a patient's scalp. Standard of care is resection of lesions. We report a case of a 74-year-old man with a known diagnosis of Brooke-Spiegler syndrome which is a genetic syndrome that results in multiple recurrent cylindromas. He had approximately 70 prior resections to remove recurrent lesions with multiple grafts. After a large scalp recurrence, with multiple satellite areas, he preferred radiation to the largest site for no-surgical management. After an excellent clinical response, this led to him electing for total scalp irradiation to the remaining sites. He now has a complete response to all remaining sites.